2020
DOI: 10.21203/rs.3.rs-61027/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of staged surgical treatment for cubitus valgus after non-union of lateral condylar fracture of distal humerus in older children

Abstract: Background: The purpose of this study was to investigate the effect of staged surgery (open reduction/internal fixation and osteotomy) for cubitus valgus after non-union of lateral condylar fractures of the distal humerus in older children.Methods: From January 2010 to January 2013, 9 patients were treated with two-staged surgery (open reduction/internal fixation and osteotomy). The study included 5 males and 4 females, with a mean age of 12.7 years. The interval from fracture to the first surgery was 8.2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…[3][4][5]9,12,19,23 Others did not do it and reported spontaneous recovery, where they owed this improvement to the gained laxity of the ulnar nerve after doing the corrective osteotomy. 11,18 In this study, we did not do any ATUN for the included cases, and we reported gradual spontaneous clinical improvement in all the cases presented with preoperative UND.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…[3][4][5]9,12,19,23 Others did not do it and reported spontaneous recovery, where they owed this improvement to the gained laxity of the ulnar nerve after doing the corrective osteotomy. 11,18 In this study, we did not do any ATUN for the included cases, and we reported gradual spontaneous clinical improvement in all the cases presented with preoperative UND.…”
Section: Discussionmentioning
confidence: 72%
“…Lately, in the last 30 years a plethora of studies published urging for osteosynthesis of the nonunited LHC, corrective osteotomy, and ATUN as a 1-stage surgery. [2][3][4][5][6][7]9,10,[16][17][18] This treatment strategy may not be convenient nor reproducible for long-standing cases of LHC nonunion with distorted elbow anatomy that requires special surgical tracts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations